CONSTRAINTS AND STRATEGIES OF ISSUING MUNICIPAL SUKUK IN INDONESIA - Muhammad Maulana Hamzah; Lukman M Baga; Imam Teguh Saptono (IAIN Batusangkar, 2022)
The purpose of this paper is to analyze the potential of Islamic municipal bonds in Indonesia focused on its constraint and strategy using Analytic Network Process (ANP). Methodology proceeded by literature research to construct a model and in-depth interview with practitioners and regulators both on government and sharia perspective to fully understand and develop an appropriate ANP Network. The experts are divided into two categories as direct relation and non-direct relation experts. The constraints are divided into five nodes, they are political risk, trust between stakeholders, lack of sharia knowledge, law constraint and risk of municipal loan. While the strategies contain of building trust, sharia education, comprehensive law basis, market strategy, and strategy of product innovation. Islamic municipal bonds may be developed by implementing comprehensive law basis as primary strategy to provide the need of law basis as main constraint. Both main constraint and strategy are agreed by all experts except BPK which is more concern in risk of municipal loan.